GRÆNSELØS STRAF: Om grønlandsk indsathed i et dansk fængsel - Møller, Julie Rahbæk; Spielman, Marlène Elisabeth M. J. (Tidsskriftet Antropologi, 2008)
The fi eldwork upon which this article is based took place among Greenlandic inmates in 2005 in two different prisons, Anstalten ved Herstedvester, Denmark and Anstalten for Domfældte in Nuuk, Greenland. We set out to investigate the affects of being sent from Greenland to Anstalten ved Herstedvester to serve a sentence of indefi nite time. Analytically we combine the two places into one social space, as our informants in Anstalten ved Herstedvester experience the one place through the other. They have all served a sentence in prisons in Greenland and they combine these experiences in understanding their present context. Even though the structure of Anstalten ved Herstedvester is characterized by transparent boundaries and the opposite applies to Anstalten for Domfældte in Nuuk, the prisoners all have diffi culties navigating in the social space. In Herstedvester the rare visits and leaves become a mediator of life inside and outside society. Even though these are desired, they are also experienced as expressions of a life, which is diffi cult to imagine since they feel locked in time and space. Their experience of time is characterised by permanance, which creates ignorance and insecurity, and they feel locked in time and without agency because of the encircled social space. “Home” is another important element of life in prison, but one that almost impossible to obtain. The convicts fi nd a feeling of at-homeness by smoking marijuana. However, some of our informants chose to stop smoking and were thereby able to receive a reduction of their time in prison.